Surreptitious Advertising as an Act of Unfair Competition - Zawadzka, Joanna (Kryptoreklama jako czyn nieuczciwej konkurencji, 2023)
This article presents the issue of surreptitious advertising against the background of the provisions of the Act on Combatting Unfair Competition. The paper presents an analysis of issues related to advertising, surreptitious advertising and the act of unfair competition. Surreptitious advertising is thus characterized as an act of unfair competition. The author also focused on the issue of surreptitious advertising n social media, which is a relatively new phenomenon that raises doubts in legal terms. The paper also describes the civil liability of entrepreneurs for committing an act of unfair competition in the field of surreptitious advertising. Problems with the creation of a uniform definition of advertising are indicated, which in turn cause difficulties in determining the definition and scope of surreptitious advertising. As a result of the analysis, the lack of a comprehensive legal act regulating the fight against unfair market practices and applicable to all trading participants was negatively assessed. This article is based mainly on the Act on Combatting Unfair Competition of 16th April 1993, as well as Polish and EU legal acts, court decisions, scientific literature, and also codes and recommendations created by governmental and non-governmental organizations.
Ekonomia XXI Wieku = Economics of the 21st Century, 2023, Nr 26, s. 38-48
Keywords: surreptitious advertising; act of unfair competition; advertising; unfair competition; kryptoreklama; czyn nieuczciwej konkurencji; reklama; nieuczciwa konkurencja